THEORY OF ANALYSIS OF ERRORS IN LEARNING FOREIGN LANGUAGE (Pedagogy of Higher and Secondary Education, 2008)
The article investigates some important moments of the theory of error analysis which arose in the 60-70s in the West as an applied research branch of linguistics directed to more successful teaching as well as learning of the foreign language.